The Effect of Different Periods of Enamel Microabrasion on the Microleakage of Class V Glass-Ionomer Restorations - Mohammadi-Bassir, Mahshid; Ebadi, Shabnam; Fahimi, Mohammad Amin (Journal of Dental School, 2019)
Objective: Removal of enamel superficial layer during microabrasion treatments may adversely affect sealing ability of the restorative materials. The aim of this study was to measure the effect of different periods of enamel microabrasion on the microleakage of class V glass-ionomer restorations. Methods: This in vitro experimental study was conducted on 96 Class V cavities which had been prepared on the buccal and lingual surfaces of 48 sound human premolars. After conditioning with 10% polyacrylic acid (GC, Tokyo, Japan) one half of the cavities were restored with the conventional glass-ionomer (Fuji II GC, Tokyo, Japan) and another half with resin-modified glass- ionomer (Fuji II LC GC, Tokyo, Japan). Finishing and polishing were performed after 24 hours and the teeth incubated for 2 weeks (37°C and 100% humidity).Then the teeth were classified into eight groups (n=12). Microabrasion treatment was performed with Opulster (Ultradent product Inc, South Jordan, UT, USA) in 0(control no treatment), 60, 120 and 180 seconds. Then teeth were thermocycled between 5°C-55°C (×1000), immersed in 0.5% basic-fushin solution (24h) and sectioned longitudinally in bucco-lingual direction (n=192). Dye penetration was examined with stereomicroscope (×40). Microleakage scores were statistically analyzed by Kruskal-Wallis test while the paired comparisons were done using Mann-Whitney U test. Results: The mean microleakage scores were significantly increased following increased microabrasion times in occlusal margin in FU II (p<0.009) and FU II LC (p<0.02) and in gingival margin in resin-modified glass-ionomer (p<0.04). Conclusion: In Fuji II restorations after microabrasion in occlusal margins, microleakage increased up to 120s but in gingival margins no significant difference were seen. In Fuji II LC restorations after microabrasion in occlusal margin, microleakage from 60s up to 180s was significantly increased. In gingival margin with increasing the time up to 180s microleakage increased.